PRE-OPERATIVE STAGING OF RENAL CELL CARCINOMA : SPIRAL CT VERSUS PATHOLOGICAL CONSIDERATIONS. (Iraqi Journal of Medical Sciences, 2016)
Background: Renal cell carcinoma (RCC) is the commonest renal malignancy, comprising 85-90% of all malignant renal tumours and represents 3% of all adult malignancies. The prognosis of RCC depends on the size, stage, and grade of the tumor. CT has proved to be the most important imaging technique for the evaluation of renal lesions and the preoperative staging of renal cell carcinomas.Objective:The aim of our study was to evaluate the accuracy of spiral CT in the preoperative assessment of patients with renal cell carcinoma correlated with histopathological findings.Patients and methods: Between February 2008 and September 2009, a prospective study included 40 patients (age range, 36–66 years; 28 men, 12 women) with solid renal masses. All the patients were diagnosed by CT as having renal cell carcinoma, underwent total nephrectomy & proved to be renal cell carcinoma at histopathlogical examination. In all patients, initial CT images were obtained without administration of contrast material, 100ml of Intravenous contrast material was administered, a repeated scan was done 120 seconds after contrast injection, both scans should covered the entire volume of the abdomen. Percentage of the parameters used in the study was calculated. Diagnostic accuracy of CT in staging renal cell carcinoma was calculated.Results: The study included 40 patients (28 men, 12 women) with solid renal masses. Tumor size ranged from 1.7 to 6.5 cm (mean size, 3.1 cm). All the patients showed evidence of contrast enhancement by about 47HU.Thirty seven patients (92.5%) show heterogeneous enhancement while only 3 patients (7.5%) show homogenous enhancement. Calcification was seen in 10 patients (25%). A pseudocapsule was present in 16 patients. Lymph node (LN) involvement with adenopathies larger than 1 cm in diameter was found in 7 patients (17.5%), only one patient (2.5%) show false negative diagnosis, the over all diagnostic accuracy of LN detection was 83%. Renal vein or inferior vena cava thrombosis was detected in 8 patients (20%), diagnostic accuracy was 87.5%. The overall diagnostic accuracy of CT in staging renal cell carcinoma was 90% (36 out of 40).Conclusions: CT is an excellent imaging technique for the evaluation of solid renal masses and the preoperative staging of renal cell carcinomas. CT has some difficulty in differentiating T3a from T2. CT has a limited ability to identify lymph node involvement by malignancy because it is still based on only size criteria, with 10 mm as the limiting size for normal nodes. Keywords: Spiral CT, pre-operative staging, renal cell carcinoma.
Keywords: Spiral CT; preoperative staging; renal cell carcinoma